1992
DOI: 10.1021/j100203a055
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and mechanistic study of the reaction of atomic chlorine with dimethyl sulfide

Abstract: 4) Orban, M.; Kijrb, E. K b b , E.; Noyes, R. M. J. Am. Chem. Soc. 1972, 94, Trans. 1992,88, 917. S = 2 k~l / k~6 / &~3 &~ = 9.52 x 10" b = 2kB6kB9[R]/k~lkW[BrOS-] = 0.545 K 3 k~z / k~l = 1.6 6 = k~l / 2 k~6 = 3.33 x r = k~i k~a / k~k~s = 0.101 Q = 2 k~s k~/ k~, ' = 0.0101 0 = kB,/kB6 = 1.667 x lo3 B = k~3 / 2 k~6 = 500 T,,, = kW[Br03-]trea = 3.91t,/s Repistry No. BrO,-, 15541-45-4; gallic acid, 149-91-7; ferroin, 14708-99-7.Timaresolved fluorescmCe detection Of Cl(9j) following 266-nm laser flash photd~is Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
139
4

Year Published

1995
1995
2008
2008

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(163 citation statements)
references
References 11 publications
20
139
4
Order By: Relevance
“…The minimum detection limits for Ar, DMS and Cl 2 were estimated as 1x10 11 , 3.5x10 11 and 4x10 11 molecules cm -3 respectively. Also for these three gases the pressure range over which the photoelectron signal was linear with pressure in the flow tube was 1x10 11 -1.1x10 14 , 3.5x10 11 -1.6x10 13 and 4x10 11 -1x10 14 molecules cm -3 respectively. (These experiments set the detection limit as a signal : noise ratio of 2 with an integration time of 1 sec.…”
Section: Detection Systemmentioning
confidence: 85%
See 3 more Smart Citations
“…The minimum detection limits for Ar, DMS and Cl 2 were estimated as 1x10 11 , 3.5x10 11 and 4x10 11 molecules cm -3 respectively. Also for these three gases the pressure range over which the photoelectron signal was linear with pressure in the flow tube was 1x10 11 -1.1x10 14 , 3.5x10 11 -1.6x10 13 and 4x10 11 -1x10 14 molecules cm -3 respectively. (These experiments set the detection limit as a signal : noise ratio of 2 with an integration time of 1 sec.…”
Section: Detection Systemmentioning
confidence: 85%
“…Stickel et al (13), in a study of reaction (2) using time-resolved detection of Cl atoms, reported that the branching ratio of reaction (2a) approaches unity with decreasing total pressure and k 2 increases with pressure. Both reactions (2a) and (2b) are expected to have large rate constants, as they proceed without a barrier, whereas reaction 2c, decomposition of (CH 3 ) 2 SCl to CH 3 and CH 3 SCl, is very slow because it has a high activation energy barrier of ≈18 kcal.mol -1 (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The values obtained were used along with the thermal corrections obtained from the frequency calculations, to calculate the value of Δ r H o at 298 K for reactions (8) - (15) and reactions (17) and (18).…”
Section: Computationsmentioning
confidence: 99%